An eight-element MIMO antenna system supporting dual bands for 5G mobile, FSS, and DBS communication - Al Gburi, Ahmed Jamal Abdullah; Mistri, Raj Kumar; Singh, Ajit Kumar; Mahto, Santosh Kumar; Sinha, Rashmi; Alhassoon, Khaled; Ismail, Mohd Muzafar (Electromagnetics Academy, 2024)
This article presents an 8 × 8 Multiple-Input Multiple-Output (MIMO) antenna system that operates in two frequency bands: 3.4–3.8 GHz and 10.5–14.0 GHz. The core element of this antenna system is a rectangular patch with a line slot. To assess the diversity performance of this MIMO antenna, various parameters like S-Parameters, Envelope Correlation Coefficient (ECC), Mean Effective Gain (MEG), Channel Capacity Loss (CCL), Total Active Reflection Coefficient (TARC), and Channel Capacity (CC) were used. The study demonstrates a strong alignment between measurement and simulation results. The article thoroughly analyzes the simulated and measured performances of the lower band (LB) (3.4–3.8 GHz) and upper band (UB) (10.5–14.0 GHz). In the LB, the measured values for parameters such as reflection coefficient, mutual coupling coefficient, TARC, total efficiency, ECC, MEGi-MEGj, CCL, and CC all surpass or equal specific benchmarks. Specifically, these values are better than −6 dB, 10 dB, −11 dB, 56%, 0.15, 0.83 dB, 0.275 bps/Hz, and 38 bps/Hz, respectively. For the UB, the values are also quite favorable, exceeding or closely matching key criteria: −6 dB, 10 dB, −5 dB, 40%, 0.2, 1.6 dB, 0.55 bps/Hz, and 33.6 bps/Hz. These findings suggest that the intended MIMO antenna meets the necessary conditions for both the LB and UB regions. As a result, it appears to be a promising choice for applications in 5G mobile networks and satellite communications, including Direct Broadcast Satellite (DBS) and Fixed Satellite Services (FSS).